IMPLEMENTATION OF MIND MAPPING LEARNING STRATEGIES TO IMPROVE THE CREATIVITY OF STUDENTS SMA NEGERI 1 KUTA UTARA - Ni Kadek Rini Purwati; Ni Kadek Mesy Wulandari (Indonesian Journal of Educational Development (IJED), 2023)
Creativity is one of the 4C skills that is required to be increased in learning cycle in this 21st century. However, the improvement of students’ creativity in learning cycle has been not completely implemented which is causing lowered creativity of the students. This fact is supported by the average value of creativity obtained by students in class XI MIPA 6 in the pre-cycle, which is 40% (less creative). Based on these problems, the implementation of strategy that is suitable to overcome this problem is mind mapping learning strategies. The type of research used is PTK, which has four stages, namely planning, action, observation, and reflection. Based on the results of the study, it was found that there was an increase in students’ learning creativity after the mind mapping has been implemented as seen from the results of the analysis of the observation sheet which initially was only 40% to 64%, and finally reached 84% in cycle II. The improvement in students' learning creativity was also seen from the increasing to the average value of mind mapping results made by students, which is 78 in cycle I, increasing to 98 in cycle II. Thus, the implementation of mind mapping method was fulfilled and the research hypothesis was proven since the application of mind mapping learning strategies was able to increase the learning creativity of students in class XI MIPA 6 SMA Negeri 1 Kuta.